Longitudinal analysis of antibody dynamics in COVID-19 convalescents reveals neutralizing responses up to 16 months after infection - Yang, Yang; Yang, Minghui; Peng, Yun; Liang, Yanhua; Wei, Jinli; Xing, Li; Guo, Liping; Li, Xiaohe; Li, Jie; Wang, Jun; Li, Mianhuan; Xu, Zhixiang; et al. (Nature microbiology, 2022)
Elucidating the dynamics of the neutralizing antibody (nAb) response in coronavirus disease 2019 (COVID-19) convalescents is crucial in controlling the pandemic and informing vaccination strategies. Here we measured nAb titres across 411 sequential plasma samples collected during 1–480 d after illness onset or laboratory confirmation (d.a.o.) from 214 COVID-19 convalescents, covering the clinical spectrum of disease and without additional exposure history after recovery or vaccination against SARS-CoV-2, using authentic SARS-CoV-2 microneutralization (MN) assays. Forty-eight samples were also tested for neutralizing activities against the circulating variants using pseudotyped neutralization assay. Results showed that anti-RBD IgG and MN titres peaked at ~120 d.a.o. and subsequently declined, with significantly reduced nAb responses found in 91.67% of COVID-19 convalescents (≥50% decrease in current MN titres compared with the paired peak MN titres). Despite this decline, majority of the COVID-19 convalescents maintained detectable anti-RBD IgG and MN titres at 400–480 d.a.o., with undetectable neutralizing activity found in 14.41% (16/111) of the mild and 50% (5/10) of the asymptomatic infections at 330–480 d.a.o. Persistent antibody-dependent immunity could provide protection against circulating variants after one year, despite significantly decreased neutralizing activities against Beta, Delta and Mu variants. In conclusion, these data show that despite a marked decline in neutralizing activity over time, nAb responses persist for up to 480 d in most convalescents of symptomatic COVID-19, whereas a high rate of undetectable nAb responses was found in convalescents from asymptomatic infections. A longitudinal analysis of the neutralizing antibody response dynamics in 214 COVID-19 convalescents up to 16 months after infection shows that despite substantial declines in antibody levels over time, they could still provide protection against circulating variants even after one year of infection in most individuals, although neutralizing activities were reduced, particularly against Beta, Delta and Mu SARS-CoV-2 variants.